Accessibility of Massive Open Online Courses in Computer Sciences and Programming for Persons with Disabilities - E. A. Kosova; A S. Gapon; K. I. Redkokosh (Открытое образование (Москва), 2020)
Purpose of research. The work deals with accessibility assessment of the Russian-language massive open online courses (MOOCs) in computer science and programming. Recent studies show that MOOCs have multiple web accessibility mistakes, both from the side of the platform and/or the authors’ content. The accessibility of MOOCs in computer science and programming has not been studied yet. At the same time, the specifics of online courses on programming require greater attention to the web content accessibility for persons with disabilities, especially in a program code.Material and methods. The selection of MOOCs was carried out in July 2020 by browsing catalogs of platforms with Russian-language content. Automatic web accessibility analysis was performed using the WAVE online tool. Checklists with a quaternary assessment system for 69 features were utilized for the expert accessibility analysis. Three experts evaluated overall accessibility of the platforms, accessibility of video lectures, digital documents, tests and program code. Results. 65 MOOCs in computer science and programming were found (Coursera 32, Stepik 33). All courses have web accessibility mistakes. Most of the errors are related to the common accessibility of the platforms. As a result of the automatic and expert checks, the following errors were found: low contrast between the background and the text; navigation errors related to the missing labels in attributes; empty links and buttons; lack of alternative text for links and images; form identification errors; lack of custom web page settings; errors in keyboard access to media players; errors of the page structure and page reading logic, creating playback problems by assistive technologies and text browsers. Errors in authors’ content are related to the incompetence of the MOOCs authors and developers in the field of web accessibility. The most common mistakes are: lack of lecture notes that are equivalent to video; incorrect wording of hyperlinks; lack of software-defined structure of the documents; the use of fragments in the content unreadable by the screen reader. Assistive technology almost always reproduces the code with errors and gaps, and embedded compilers have impaired access to the visual interface and feedback.Conclusion. To improve the web accessibility of the MOOCs in computer science and programming, the following steps should be carried out: 1) common platform accessibility errors should be fixed and the content of the published MOOCs should be brought in line with the Web Content Accessibility Guidelines (WCAG) 2.1; 2) only those courses should admit for publication on platforms, that have passed the web accessibility assessment procedure; 3) MOOCs’ production teams should be trained in the basics of web accessibility and develop new courses in accordance with WCAG 2.1; 4) attention should be paid to the creation of ergonomic compilers in accordance with the requirements for accessible software and web development tools.